The first report of the occurrence and petrography of garnet-orthopyroxene granulite from Oku-iwa Rock in the Lützow-Holm Complex, East Antarctica - Kitano, Ippei; Toyoshima, Tsuyoshi; Ishikawa, Masahiro; Katori, Takuma; Hokada, Tomokazu (2020)
The 11th Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Poster presentations, Mon. 16 Nov. - Fri. 18 Dec. conference object